PENGARUH JARAK SARAD DAN VOLUME KAYU YANG DISARAD TERHADAP PRODUKTIVITAS TRAKTOR PENYARADAN - Dulsalam Dulsalam; Sukanda Sukanda (Jurnal Penelitian Hasil Hutan, 1990)
An inveatigation on the effect of alcidding diatance and •kidded log volume on the productivity of kidding tractor um carrkd  out at a forest company in Jambi in 1986. Caterpillar D1 G trac~ors were elected randomly and their working time and skidded log volume were obaervedthrough work time atudy. The purpoH  of thia invatigation ia to find  out the effect of kidding  diatance and skidded log volume on the productivity   of kidding  tractors. The invati1Qtion  coma  to the fotlOwing concluaioru.                              1.  The owrace of skidding diatance wa  8.24 hm with  standard error of  0.2tJ66 hm while  the average of idded log volume IDOi  9.08 m8 with. 0.3173 m3 atandard error.                                                                     J.  The a~        productivity of skidding  tractor  waa  92.09 m8 hm/hour  with  atandard error of  6.8406 m8 hm/hour.3. The Niationahip  between tractor productivity   (Y)  and •kidding  diatance (X 1) and kidded  log volur.ne (X2) can beupraaed   in the li~       r.nultipie Ngreuion: Y   -   48.1670 + 16.0704X1   + 9.6176 Xa with R2 •  0.71604. The effects of  kidding  diatanca  and •kidded  log . voluma  on the productivity of •kidding  tracton  are aigniffcant.TM  tractor productivity   increaaedproportionaUy  when the •kidding. diatance and •kidded• log volume increaed. It  therefore recommended to make the •kidded loga as long as poaible  GI  far  GI   the tractor can handle.